European Works Councils and industrial relations in Europe: East-West comparison (Geneva, 1999)
"Compares the recent experiences of the implementation of Directive 94/45 in EU member states and highlights the problems and issues that the Directive poses for industrial relations systems of selected Central and East European countries."